Characterization of x-rays pulses from a hundred joules plasma focus to study its effects on cancer cells. (May 2016) - Jain, J.; Moreno, J.; Avaria, G.; Pavez, C.; Bora, B.; Izurieta, M. J. Inestrosa; Diez, D.; Alvarez, O.; Tapia, J.; Marcelain, K.; Armisen, R.; Soto, L.
Abstract: With the purpose to study the effects of pulsed x-rays radiation on cancer cells, the total doses of x-ray pulses and the temporal duration of the pulse has been characterized in a hundred joules plasma focus device (PF-400J, 130 kA achieved in 300ns, 30 kV, 880 nF, 38 nH). TLD dosimeters were located outside of the discharge chamber, at 96 mm from the anode top. In addition, two photomultipliers with plastic scintillator were located in axial and radial directions. From the statistical analysis of the TLD and photomultiplier signals, was possible to estimate that a single shot has a total dose of the order of 30±15 µSv with a duration of the order of 12±3.6 ns at FWHM. Preliminary experiments using MCF7, a breast cancer cell line, were performed. Cells were irradiated at 96 mm from the anode top with 300 cumulative x-ray shots and cell proliferation was evaluated at 24, 48 and 72 hours later.